A comparative study of transmissibility factors of traditional and pneumatic dumper seats using one-third octave band analysis. (October 2020) - Mandal, Bibhuti B; Bhattacharjee, Ashis; Prajapati, Shivkumar; Hussain, Syed Aftab
Severity of exposure to whole-body vibration of vehicle drivers depends on multiple factors including type of vehicle suspension or quality of seats. The study presents analysis of seat vibrations of two different types of dumpers in opencast mines. Since health guidance provided in ISO 2631-1997 are only indicative, seat effective amplitude transmissibility factors along with one-third octave-band analysis of vibration signals have been considered as more effective information for control measures. Vibration characteristics of conventional seats ( n = 3) with rigid frame and those with pneumatic suspensions ( n = 3) have been compared during their use in mines. A (8) values ranged from 0.66 to 1.41 m/s 2 . All the six operators had shown moderate to higher health risk but this may vary since both intensity and durations of exposure frequently change during the operators' employment. Vibration signals from a mono-axial accelerometer (z′) placed on the cabin floor was captured in addition to three channel vibration data (x, y and z) of a seat pad accelerometer placed on the vehicle seat. Transmissibility analysis of vibration signals from cabin floor to seat surface showed that the three pneumatic seats resonated in the range of 1.6–2.5 Hz in the z axis. There was significant attenuation of vibration energy ranging from 37% to 63% at 4 Hz which is important in the context of spinal injuries. The seat effective amplitude transmissibility values (%) in the resonating frequencies ranged from 119% to 173%. Interestingly, the conventional seats resonated at 4–5 Hz and the corresponding seat effective amplitude transmissibility (%) values were varying from 128% to 163%. This resonance at 4 Hz is in sharp contrast with the behaviour of pneumatic seats. It is recommended that vibration transmissibility should be considered as a major design parameter for mining vehicle seats.